2020
DOI: 10.1042/bsr20200221
|View full text |Cite|
|
Sign up to set email alerts
|

Fingolimod inhibits proliferation and epithelial–mesenchymal transition in sacral chordoma by inactivating IL-6/STAT3 signalling

Abstract: Purpose: To explore the sensitivity of the immunosuppressive agent fingolimod (FTY720) in chordoma and determine whether it can serve as an appropriate alternate treatment for unresectable tumours in patients after incomplete surgery. Methods: Cell viability assays, colony formation assays and EdU assays were performed to evaluate the sensitivity of chordoma cell lines to FTY720. Transwell invasion assays, wound healing assays, flow cytometry, cell cycle analysis, immunofluorescence analysis, We… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 48 publications
0
4
0
Order By: Relevance
“…Sarilumab, another antibody against IL-6 receptor used in rheumatoid arthritis (Lamb and Deeks, 2018), is being tested in a multicenter, double-blind, clinical phase 2/3 in patients with severe COVID-19 (NCT04315298) (Sanders et al, 2020). Other drugs that showed potential inhibition of IL-6 related JAK/STAT pathway are: Fingolimod which showed to inhibit proliferation and epithelial-mesenchymal transition in sacral chordoma by inactivating IL-6/STAT3 signaling (Wang et al, 2020c), a clinical trial in COVID-19 patients is ongoing (NCT04280588, Phase2) (COVID-19 Clinical Trials, 2020); glatiramer acetate showed potential to downregulate both IL-17 and IL-6 in the central nervous system in an autoimmune encephalitis model (Begum-Haque et al, 2008).…”
Section: Tocilizumab and Other Il-6 Receptor Inhibitorsmentioning
confidence: 99%
See 1 more Smart Citation
“…Sarilumab, another antibody against IL-6 receptor used in rheumatoid arthritis (Lamb and Deeks, 2018), is being tested in a multicenter, double-blind, clinical phase 2/3 in patients with severe COVID-19 (NCT04315298) (Sanders et al, 2020). Other drugs that showed potential inhibition of IL-6 related JAK/STAT pathway are: Fingolimod which showed to inhibit proliferation and epithelial-mesenchymal transition in sacral chordoma by inactivating IL-6/STAT3 signaling (Wang et al, 2020c), a clinical trial in COVID-19 patients is ongoing (NCT04280588, Phase2) (COVID-19 Clinical Trials, 2020); glatiramer acetate showed potential to downregulate both IL-17 and IL-6 in the central nervous system in an autoimmune encephalitis model (Begum-Haque et al, 2008).…”
Section: Tocilizumab and Other Il-6 Receptor Inhibitorsmentioning
confidence: 99%
“…Sarilumab (Lamb and Deeks, 2018;Sanders et al, 2020) IL-6 Receptor Inhibitor NCT04280588, Phase2 Fingolimod (Wang et al, 2020c;COVID-19 Clinical Trials, 2020) inactivating IL-6/STAT3 pathway NCT04280588, Phase2…”
Section: Nct04261517 Phase 3 (+)mentioning
confidence: 99%
“…It plays a crucial role in promoting tumor metastasis and EMT process. The S1PR1 antagonist FTY720 can significantly inhibit EMT program by inactivating STAT3 signaling (82,83), further modulating the resistance of cancer cells to therapy. Several studies have shown that S1PR1-mediated sustaining activation of STAT3 is of critical importance in proliferation and multidirectional differentiation of CSCs, which is closely associated with acquired radioresistance in a variety of malignancies such as pancreatic cancer and glioma (28)(29)(30).…”
Section: Other Relevant Molecular Mechanismsmentioning
confidence: 99%
“…The cells were cultured in serum-free medium overnight before the initiation of the experiments. For migration assay, 1 × 10 5 cells in 0.25 mL of serum-free medium were seeded into the upper chamber [38] and 0.5 mL of medium with 10% FBS was added to the lower chamber and incubated at 37 °C for 24 h. For the invasion assay, 70 μL of 1:10-chilled serum-free mediumdiluted Matrigel (Catalog No. 354234, BD Biosciences, NJ, USA) was precoated in the upper chamber and incubated in a humidified incubator at 37 °C for 60 min.…”
Section: Cell Migration and Invasion Assaymentioning
confidence: 99%